Total Total Ionization Cross Sections due to Electron Impact of Carbon Tetrafluoride from Ionization Threshold to 10 MeV - Dr. Kiran Pal; Dr. Amrita; Dr. Yogesh Kumar; Dr. Manoj Kumar; Dr. Pramod Kumar (International Journal of Engineering and Management Research, 2022)
Modified Khare-BEB model has been used to calculate the electron impact ionization cross section for carbon tetrafluoride (CF4) from ionization threshold to 10 MeV. The collisional parameters CRP and also has been calculated. The calculations are compared with available experimental data . A good agreement is found among the present results, other previous calculations, and experimental data.